Risks Allocation in PPP Projects According to Cost of Risk, Partners’ Attitude and Partners’ Ability in the UAE - SALEH, FADI ALHAJ (2017)
Public-private partnership is adopted worldwide by governments to procure public projects and services, and to deliver value for money using private finance. This can be achieved by creating a “win-win” situation and balancing the parties’ interests to achieve the optimum risks allocation. Purpose – This study has been devoted to finding out the criteria that influence risk allocation in PPP projects to optimize value for money in public-private partnership projects. Design/methodology/approach – A comprehensive literature review was carried out first and then a critical review and a comparative analysis were employed to identify a list of risks and criteria impacting the risk allocation. Finally, an empirical questionnaire survey was conducted with PPP experts in the UAE to understand and analyze their feedback/opinions about the proposed criteria and their impacts on risk allocation. Findings – The study includes developing a comprehensive list of risk events and a list of criteria that affect the risk allocation. In Addtion, the findings show that all risks are impacted by partners’ ability, eighteen risks are influenced by partners’s attitude, and only twelve risks are impacted by risk cost. The risk allocation is not a static process and will never overstate, as such, the study concludes that the risk allocation should be amended according to the proposed criteria during the performance of the contract to allow the decision makers to re-allocate the risk properly in order to achieve optimum risk allocation. Research Implications – The paper was limited to proposing theoretically the criteria and exploring their impacts. Therefore, the next step is to examine practically the implementation of the proposed criteria in order to record and analyze the performance, effectiveness, and empirical results of this framework. Practical Implications – Risk allocation in PPP projects should be a flexible process, that means that risk allocation should be adjusted according to the changes in the proposed criteria. This will assist both partners to better understand the risk allocation, minimize the contract negotiations, and reduce the number of disputes between the partners during the concession period. Originality/Value – To guarantee the success of PPP projects, it is essential to achieve optimum risk allocation. In practice, optimum risk allocation is rarely attainable and many frameworks and methodologies have been proposed but still the issue is controversial. To this end, this paper proposes to allocate the risks according to the proposed criteria. Study Limitations - The paper is limited to evaluating the impact of risk costs, partners’ attitude, and partners’ ability on the risk allocation of design risks, construction risks and operation risks. Therefore, a further study is required to evaluate the impact of the rest of the criteria and to analyze the impact on the rest of the risks. Also, a future study is needed to analyze the interactions between the proposed criteria and to rank them according to their influences.